Financialization and neoliberalism and the fall in the labor share: a panel data econometric analysis for the European Union countries - Barradas, R. (Review of Radical Political Economics, 2019)
This paper conducts an empirical analysis of the relationship between financialization and neoliberalism and the labor share using panel data composed of twenty-seven European Union countries over nineteen years (from 1995 to 2013). Adopting a Kaleckian perspective, framed in the post-Keynesian literature, financialization and neoliberalism exert a negative influence on the labor share through three different channels: the change in the sectorial composition of economies (the increasing importance of financial activity and the decreasing importance of general government activity), the proliferation of shareholder value orientation, and the deterioration of general workers’ bargaining power. We estimate a labor share equation with the traditional variables (lagged labor share, technological progress, globalization, education, and output growth) and four further measures of financialization and neoliberalism (financial activity, general government activity, shareholder value orientation, and the trade union density rate). The findings show a disruptive relationship between financialization and neoliberalism and the labor share in European Union countries, mainly through the channels of general government activity and shareholder value orientation. It is also found that financialization and neoliberalism have contributed to a fall in the labor share in European Union countries. The technological progress was the main driver of the fall in the labor share in European Union countries, while the output growth was the main supporter. This suggests that the trend of decline in the labor share could intensify in the future taking into account the fears of potential secular stagnation in the current era of financialization and neoliberalism.